A high-fat diet disrupts the hepatic and adipose circadian rhythms and modulates the diurnal rhythm of gut microbiota-derived short-chain fatty acids in gestational mice - Ding, Lu; Liu, Jieying; Zhou, Liyuan; Jia, Xinmiao; Li, Shunhua; Zhang, Qian; Yu, Miao; Xiao, Xinhua (Frontiers in Nutrition, 2022)
The prevalence of gestational obesity has reached epidemic proportions. Evidence supported that the interactions between the gut microbiota and circadian clocks far reached, affecting host metabolism. Our study aimed to investigate the effect of a high-fat diet (HF) on the hepatic and adipose circadian rhythms in gestational mice and to explore the role of gut microbiota-derived short-chain fatty acids (SCFAs) in mediating the effects. C57BL/6 female mice were randomly fed a standard chow diet (Ctr) or HF prior to and during pregnancy. Samples were collected every 4 h over 24 h (six time points), and 16S rRNA and metabonomics were carried out. Rhythmic patterns were identified and compared using CircaCompare. The results showed that the HF before and during pregnancy significantly induced obesity and worsen glucose tolerance, insulin sensitivity, and lipid metabolism in the gestational mice. Furthermore, the HF significantly disrupted the rhythmic pattern of hepatic and adipose circadian clock genes and downstream metabolic genes. Importantly, our results revealed that the HF altered the diurnal rhythm of the gut microbiota in a diverse manner, which was assessed across three categories: phase shift, loss rhythmicity, and gained rhythmicity. We report here, for the first time, a parallel alteration of the rhythmic phase of butyric acid and butyrate-producing Clostridiaceae_1, which was confirmed by a positive correlation between them. Overall, our research emphasized the importance of the rhythmicity of gut microbiota-derived SCFAs in mediating circadian disruption in response to the HF in gestational mice, which may provide novel insights into the prevention and treatment of gestational obesity.